Islam and Nationalism in the Formerly Soviet Central Asian Republics - Mellon, James (Journal of Conflict Studies, 2005)
ABSTRACT When the Soviet Union collapsed, the Central Asian republics, which had not really sought independence, found themselves independent. Unlike what happened in some other parts of the former Soviet Union, the regimes in power under the Soviet Union remained in power, and endeavored through authoritarian means and trying to identify themselves with nascent nationalisms to suppress opposition and seek an aura of legitimacy. These regimes sought to suppress expressions of Islam and Islamic revivalism outside of state-sponsored Islam. Particularly in the aftermath of 11 September, it has been expedient for these regimes to label non-state-sponsored Islam as Wahhabi, even though most of this Islam has been of the more moderate indigenous Hanafi school. Progress in democratization has varied among the republics but has been slow in all of them. Until the overthrow of Askar Akayev in Kyrgyzstan in March 2005, only Tajikistan, which had experienced a civil war, had changed leaders since independence. This article expresses concern that a focus on fighting terrorism may lead to a tendency to overlook issues of human rights and democratization in these states.